Exploring the Antidepressant Effect and its Molecular Mechanisms of Pattern Separation Training on Newborn Neurons - Yi Daoqin (BIO Web of Conferences)
Newborn neurons in the dentate gyrus (DG) region of the hippocampus play a crucial role in the ability to perform pattern separation, and impairments in this ability have been associated with depression. Therefore, prior research has focused on designing interventions to enhance the number and activity of new neurons as a potential antidepressant approach. However, these interventions primarily emphasize physical exercise, with few studies exploring cognitive training. This proposal outlines a series of pattern separation training exercises in mice to investigate whether such training can exert antidepressant effects by improving the number, activity, or synaptic plasticity of newborn neurons. Additionally, it aims to determine the optimal timing for the training and the specific mechanisms underlying the antidepressant effects. The expected outcome is that the proposed pattern separation training will enhance the number, activity, and synaptic plasticity of newborn neurons, leading to a prophylactic antidepressant effect. This proposal contributes to the development of cognitive training programs, including pattern separation training, and provides support for the positive effects of similar cognitive interventions on newborn neurons.